2012
DOI: 10.1177/1076029611434525
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Some Clinical Situations, Autoantibodies, and Pseudothrombocytopenia

Abstract: The widespread usage of blood count autoanalyzers has led to a major improvement in cellular hematology because of quick and accurate results found in most instances. However, spurious test results also can be observed like pseudothrombocytopenia (PTCP). In our study, we aimed to evaluate the clinical and laboratory factors associated with PTCP. Forty-six patients with PTCP and 69 healthy volunteers were enrolled in the study. Sex distribution was similar between the groups. Hospitalization, infection, the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
(25 reference statements)
0
16
0
Order By: Relevance
“…Platelet cohesion depends on the interaction between GP IIb/IIIa and fibrinogen. About 0.1% to 2% of hospitalized patients have IgG or IgM antibodies against a hidden epitope in GP IIb/IIIa which is typically inconsequential in vivo [9]. These antibodies can be associated with occult malignancies, antinuclear antibodies, antibiotics like levofloxacin and ceftriaxone, and procedures like transcatheter arterial embolization of hepatocellular carcinoma [6,7,10].…”
Section: Figure 3: Approach To Low Platelet Countsmentioning
confidence: 99%
“…Platelet cohesion depends on the interaction between GP IIb/IIIa and fibrinogen. About 0.1% to 2% of hospitalized patients have IgG or IgM antibodies against a hidden epitope in GP IIb/IIIa which is typically inconsequential in vivo [9]. These antibodies can be associated with occult malignancies, antinuclear antibodies, antibiotics like levofloxacin and ceftriaxone, and procedures like transcatheter arterial embolization of hepatocellular carcinoma [6,7,10].…”
Section: Figure 3: Approach To Low Platelet Countsmentioning
confidence: 99%
“…The biochemical profiles in EDTA-PTCP are not fully evaluated. Isik et al [20] showed that the levels of cholesterol, low-density lipoprotein, high-density lipoprotein, and triglyceride were not significantly different between the EDTA-PTCP and control groups. In this study, we found that ALT, AST, ALP, LDH, and uric acid were significantly higher in the PTCP group when compared with controls.…”
Section: Tablementioning
confidence: 99%
“…Hospitalization, medications, and underlying diseases are considered to increase the incidence of EDTA-PTCP [1,20]. For instance, EDTA-PTCP has been documented in patients with a wide variety of disorders, including autoimmune disease [15], viral [21] and bacterial infection, chronic liver diseases [15], metabolic syndromes, malignancies [15,22], and even in patients undergoing allogeneic stem cell transplantation [23].…”
Section: Tablementioning
confidence: 99%
“…Kundi et al (1) did not mention from where blood samples were obtained, what kind of sample tubes were used, or when blood samples were analyzed after venipuncture in each patient. First, the platelet count obtained from citrate-anticoagulated blood samples has been reported to be higher than that obtained from EDTA-anticoagulated blood samples (3). Second, EDTA-induced pseudothrombocytopenia due to platelet agglutination because of EDTA-induced alteration of surface glycoproteins and anionic phospholipids is an important issue when using EDTA-anticoagulated samples (4).…”
mentioning
confidence: 99%